Analisa Sistem Penyimpanan Dokumen Di UNIT Sekretariat RS Grha Kedoya Dengan Metode UAT Jakarta Barat - Arie Anini Mardiah; Sandri Sagitarius Sarumaha (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Grha Kedoya Hospital in West Jakarta faces significant challenges in document management, including medical records, financial reports, and administrative documents. This study aims to analyze the document storage system in the Secretariat Unit of Grha Kedoya Hospital using the User Acceptance Testing (UAT) method. The results show that the security, functional, and non-functional aspects of the document storage system are rated very well by respondents, with average scores of 80.4%, 81.4%, and 76.4% respectively. Despite challenges in transitioning to a digital system such as staff adaptation and infrastructure investment, the majority of respondents support this change to enhance efficiency and security. The UAT method proves effective in identifying the system's strengths and weaknesses, providing constructive feedback for improvement.